Deferred Tax On Real Profit Management With Tax Planning As Moderating - Marlina Permatasari; Estralita Trisnawati (Jurnal Akuntansi, 2022)
This research examines the.effect.of current taxes, deferred.tax.and.tax amnesty on real earnings management.and tax planning as moderating. The sample is from.the property;and;real;estate;companies;listed;on;IDX-IC during 2013 until 2019. Based on purposive sampling, the selected sample is 23 companies, the total sample is 138 observations. The hypothesis is carried out using MRA through Eviews 10. The;results;of this;study;indicate;that;current;taxes, deferred;tax;expense, ;tax amnesty;and;tax;planning have;a;positive;effect;on;real;earnings;management. In addition, this study reveals that there is moderating effect of tax planning on the relationship;between;current;tax;and deferred;tax;expense;with;real;earnings;management. In addition, management can use the results of this study as consideration in deciding whether to take real earnings management actions or not, which in turn will affect the sustainability of the company.